Formulas and calculations for drilling, production, and workover - Lapeyrouse, Norton J. (Burlington, MA : Gulf Professional, 2002)
This handy book gives you all the formulas and calculations you are likely to need in drilling operations. It is the most complete manual of its kind. Included are formulas for pressure gradient, specific gravity, pump output, annular velocity, and buoyancy factor. In addition, there are calculations for volume and stroke, slug weight, drill string design, cementing, depth of washout, bulk density of cuttings, and stuck pipe. Separate chapters deal with calculations for drilling fluids, pressure control, and engineering. Example calculations are provided throughout. Presented in easy-to-use, step-by-step order, Formulas and Calculations is a quick reference for day-to-day work out on the rig. It also serves as a handy study guide for drilling and well control certification courses. Virtually all the mathematics required out on the drilling rig is included here in one convenient source.
Includes bibliographical references and index.
Keywords: Oil wells -- Management -- Mathematics; Electronic books